Influência da geometria do martelo na determinação da força durante o ensaio de impacto Charpy-V - Kruger, Eduardo Leira [UNESP]; Tokimatsu, Ruís Camargo [UNESP] (My University, 2003)
The instrumentation applied to the Charpy test machine allows the accompaniment of the specimen answer front the impact load, in form of a sign characteristically dynamic representative of the deformation process and it fractures of material tested. The main advantages of the rehearsal conventional Charpy: low cost, manufacturing sample facilities and simple handle the machine. With the instrumentation, the number of information regarding the process of fracture of the specimen increases. In this work discusses the influence of the hammer geometry in determination of the force during the process of specimen fracture submitted to the instrumented impact test Charpy-V. The purpose is obtaining a hammer, in conformity with Norma ISO 14.556, with great sensibility to register the force during the impact. Two geometries different from hammers were instrumented and rehearsed with material of low tenacity, in this case the steel ABNT 4140 in the condition of having normalized. It could be proven as larger the sensibility of the hammer, adult will be the effects of the shock waves in the strain gages of the transducer.
Influence of the hammer geometry in the determination of the force during Charpy-V impact test
Keywords: Force transducer; Instrumented Charpy-V; Charpy impact testing; Codes (standards); Costs; Deformation; Fracture toughness; Geometry; Impact testing; Loads (forces); Materials testing; Shock waves; Transducers; Mechanics